2017
DOI: 10.1002/sctm.17-0172
|View full text |Cite
|
Sign up to set email alerts
|

Role of SDF-1:CXCR4 in Impaired Post-Myocardial Infarction Cardiac Repair in Diabetes

Abstract: Diabetes is a risk factor for worse outcomes following acute myocardial infarction (AMI). In this study, we tested the hypothesis that SDF‐1:CXCR4 expression is compromised in post‐AMI in diabetes, and that reversal of this defect can reverse the adverse effects of diabetes. Mesenchymal stem cells (MSC) isolated from green fluorescent protein (GFP) transgenic mice (control MSC) were induced to overexpress stromal cell‐derived factor‐1 (SDF‐1). SDF‐1 expression in control MSC and SDF‐1‐overexpressing MSC (SDF‐1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
30
0
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 27 publications
1
30
0
3
Order By: Relevance
“…The surprising increases in both ATV ‐MSCs recruitment and survival in current study, which are the fundamental and bottle‐neck for therapeutic efficacy in cell therapy, were mainly ascribed to the prominent effects of SDF‐1‐driven targeted homing and strong antiapoptotic properties of ATV ‐MSCs by the combination protocol. Another contributing factor for ATV ‐MSCs survival was the powerful ameliorating of intense inflammatory harsh microenvironment in the infarcted region by intensive ATV treatment with strong anti‐inflammatory and antiapoptotic effects, as in the current study, our previous studies , and the studies of others . To the best of our knowledge, this is the first report to find the remarkable enhancement of SDF‐1 expression in infarcted myocardium by intensive ATV treatment over the entire 4‐week period of AMI, and the mid‐term stage (the 2nd week) of AMI was the optimal time window period of ATV ‐MSCs transplantation with the clinically feasible combination protocol in preclinical AMI model.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…The surprising increases in both ATV ‐MSCs recruitment and survival in current study, which are the fundamental and bottle‐neck for therapeutic efficacy in cell therapy, were mainly ascribed to the prominent effects of SDF‐1‐driven targeted homing and strong antiapoptotic properties of ATV ‐MSCs by the combination protocol. Another contributing factor for ATV ‐MSCs survival was the powerful ameliorating of intense inflammatory harsh microenvironment in the infarcted region by intensive ATV treatment with strong anti‐inflammatory and antiapoptotic effects, as in the current study, our previous studies , and the studies of others . To the best of our knowledge, this is the first report to find the remarkable enhancement of SDF‐1 expression in infarcted myocardium by intensive ATV treatment over the entire 4‐week period of AMI, and the mid‐term stage (the 2nd week) of AMI was the optimal time window period of ATV ‐MSCs transplantation with the clinically feasible combination protocol in preclinical AMI model.…”
Section: Discussionsupporting
confidence: 75%
“…In the majority of preclinical and clinical studies , the most commonly used transplantation time window period is within 1 week post‐AMI , although the therapeutic efficacy of MSCs is still weak with only 2%–3% LVEF elevation . It has been reported that SDF‐1/CXCR4 axis plays a paramount role in the recruitment of implanted MSCs for cardiac repair , the natural soaring upregulation of SDF‐1 expression in infarcted myocardium in the early stage (the 1st week) of AMI can recruit more CXCR4‐expressed MSCs , although the severe inflammatory response and oxidative stress may lead to apoptosis and necrosis of the implanted MSCs. On the contrary, in the late stage (the 4th week) of AMI, the inflammation alleviates, making it easier for MSCs to survive, whereas lack of SDF‐1‐driven cell recruitment with scar formation in the infarcted region may impede the potential benefits of MSCs transplantation .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, SDF‐1 has been proven to stimulate recruitment of progenitor cells to the ischaemic tissue . SDF‐1 protein levels were increased during the first days after induction of myocardial infarction . Moreover, overexpression of SDF‐1 augmented stem cell homing and incorporation into ischaemic tissues .…”
Section: Introductionmentioning
confidence: 99%
“…SDF‐1 protein levels were increased during the first days after induction of myocardial infarction . Moreover, overexpression of SDF‐1 augmented stem cell homing and incorporation into ischaemic tissues . Interestingly, hematopoietic stem cells were shown to be exquisitely sensitive to SDF‐1 and did not react to G‐CSF or other chemokines (eg, IL‐8 and RANTES) …”
Section: Introductionmentioning
confidence: 99%